The influence of ethnicity on the reporting of intellectual capital - Noradiva Hamzah,; Norman Mohd Saleh,; Sumayah Mohamed, (Penerbit Universiti Kebangsaan Malaysia, 2015)
In the 21st century, Intellectual Capital (IC), which comprised of human, structural and relational capitals, has become a source of predictors for future performance. The role of IC for future performance prediction surpasses traditional measures, such as physical and fi nancial capital. This study investigates whether the ethnicity of directors, which include chief fi nancial offi cers, chairman and audit committees, infl uences the amount of IC disclosure at the fi rm level. This study adopts a quantitative research approach, whereby level of IC disclosure is measured based upon the content analysis of corporate annual reports from 77 technology based companies in Malaysia. Malaysia is used as the setting for this study due to its ethnic diversity and the fact that the ethnic groups, to some extent, maintain their original cultural values. A ranked regression of normal scores is utilized to examine the relationship between the levels of IC disclosure and ethnicity. The study fi nds that a signifi cant relationship exists between ethnicity of some directors and levels of IC disclosure.